Empowering family-teacher partnerships building connections within diverse communities - Coleman, Mick (SAGE, 2013)
This book prepares students to work collaboratively with families and community professionals in support of children's early education and development. Students are invited to develop a personal philosophy of family involvement to guide their work with families and to join a community of learners in relying upon their collective insights and problem-solving skills to address family involvement challenges.
Keywords: Early childhood education : Parent participation; Parent-teacher relationships : United States; Early childhood education : Parent participation; Parent-teacher relationships : United States